2010
DOI: 10.1111/j.1526-4637.2010.00802.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Demographic Variables Related to Pain in HIV-Infected Individuals Treated with Effective, Combination Antiretroviral Therapy (cART)

Abstract: In this cohort treated with cART, pain was less prevalent and less likely to be associated with HIV disease progression or treatment than indicated by studies conducted prior to the widespread use of cART.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
37
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 11 publications
4
37
1
Order By: Relevance
“…Although elevated with respect to the general population, this finding is in line with prior research on HIV-positive patients, which has gauged pain prevalence to be between 40% and 80%. [1][2][3][4] Our data confirm that pain is an exceedingly common co-morbid health condition among HIV-positive individuals, including the non-elderly and those treated in an era of ARVs with lower side effect profiles. Although this study did not gather information on pain intensity or duration, prescribed pharmacotherapy to treat pain was modest, with 41.5% of those endorsing pain being untreated.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Although elevated with respect to the general population, this finding is in line with prior research on HIV-positive patients, which has gauged pain prevalence to be between 40% and 80%. [1][2][3][4] Our data confirm that pain is an exceedingly common co-morbid health condition among HIV-positive individuals, including the non-elderly and those treated in an era of ARVs with lower side effect profiles. Although this study did not gather information on pain intensity or duration, prescribed pharmacotherapy to treat pain was modest, with 41.5% of those endorsing pain being untreated.…”
Section: Discussionsupporting
confidence: 69%
“…7 A small but emerging body of literature suggests that pain experience among HIV-positive patients is associated with poor ARV adherence and reduced attendance at HIV-related care visits, 2,3,14 both of which are key behavioral components of disease management to achieve viral suppression and prevent onward transmission. 15,16 Although a handful of other studies has shown no link between pain and ARV treatment adherence, 1,13 the dearth of research on this topic precludes consensus.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2 In this chronically medically ill patient population, there is evidence that pain and nonpain symptoms are common. Estimates of pain prevalence in HIV-infected patients in the current treatment era range from 39%-55%; [3][4][5][6][7][8][9][10] however, the etiology of this pain has not been well characterized. Also, one recent study found that HIV-infected patients experience an average of eight nonpain physical and psychological symptoms, including lack of energy, numbness in the hands and feet, worrying, and feeling sad.…”
mentioning
confidence: 99%
“…17 Most studies of chronic pain prevalence in HIV-infected patients rely on queries pertaining to short time frames (1 day to 1 month), [5][6][7][8][9][10][11][12][13] or methods of screening for chronic pain that have not been validated in any clinical population. 13 Furthermore, well-validated pain questionnaires, such as the Brief Pain Inventory 18 and Multidimensional Pain Inventory, 19 have been used to study pain in patients with HIV, [5][6][7][8][9][10][11][12][13] but are not designed as screeners. As detailed questionnaires, they were designed to understand pain's impact on physical and emotional function in patients already known to have a pain condition, whether acute or chronic.…”
mentioning
confidence: 99%